Beyond community: An analysis of social capital and the social networks of Brazilian migrants in Amsterdam. (November 2013) - Roggeveen, Suzanne; van Meeteren, Masja
This article scrutinizes the social networks and the social capital invested within these, of a relatively new and understudied immigrant group in the North European context. The study shows how the social networks of Brazilian immigrants in Amsterdam are segmented along strong dividing lines, especially surrounding legal status. This segmentation has different outcomes for migrants, and within these segments, variation also exists. By analysing in-depth interviews with 30 Brazilian immigrants in Amsterdam, the study finds that a Brazilian community does not exist, and that assistance, non-assistance and a commercialization of social relations all take place at the same time among the social networks of Brazilians in Amsterdam. The analysis also uncovers some of the mechanisms related to these processes and hence adds relevant insights to the literature that studies the contexts in which immigrant social networks provide for social mobility and the contexts in which such networks do not.